An analysis of the narrative techniques of five contemporary Filipino writers - Chua, Praxedes Dy (Animo Repository, 1988)
This study is an analysis of the narrative techniques found in selected works of five contemporary Filipino writers, namely: Renato O. Villanueva, Edgardo M. Reyes, Jose Y. Dalisay, Jr., Lualhati Bautista, and Ricardo Lee. The researcher uses the Structuralist Theory of Literature which studies the narrative techniques used by the five writers in each of their works through an analysis of the narrative structure of each piece, the study of how characterization is related to the plot and how the theme or themes of the piece act as the binding element which gives unity to the artwork. The study concludes that contemporary Filipino writers use a blend of old and new narrative techniques. Characterization is clear specifically in the literary award-winning works of the five writers while stereo-typed characterization is still being used in their popular works. New techniques as psychological and psycho-social treatments of character are also used in many of their works. As socially-conscious writers, the themes commonly used in their works concern the contemporary Filipino, his dreams, his frustrations, his accomplishment and his failures and his struggle to cope with economic, social, political and religious problems. These five writers are still very much in touch with traditional writing techniques shown mostly in their popular works. The contemporary writers also use modern techniques of writing as evident in their literary award-winning works. The writer's adherence to or diversion from traditional techniques greatly affects the quality of his artistry. There is a split between the literary award-winning works of these writers and their popular works. The narrative techniques they use in their literary award winning works are far better than the techniques they use for their popular works, although this split is narrowing as these writers carry over their better writing techniques to their popular works.The fusion of the old and new techniques in the works of these five contemporary writers shows tha